Anion‐Doped Mixed Metal Oxide Nanostructures Derived from Layered Double Hydroxide as Visible Light Photocatalysts. (16th December 2012) - Cho, Seungho; Jang, Ji‐Wook; Kong, Ki‐jeong; Kim, Eun Sun; Lee, Kun‐Hong; Lee, Jae Sung
Abstract Mixed metal oxide (MMO) nanostructures co‐doped uniformly by carbon and nitrogen are synthesized for the first time by annealing a terephthalate‐intercalated layered double hydroxide (LDH) under ammonia gas flow. The interlayer gallery of LDH allows effective access of NH3 and the carbon source to its crystal lattice for a uniform nitrogen and carbon doping. Such co‐doped MMO exhibit significantly red‐shifted absorption spectra to visible light region relative to pure MMO. Photoelectrochemical water oxidation and incident‐photon‐to‐current‐conversion efficiency of LDH‐derived photocatalysts demonstrate that all the visible light absorption caused by the anion doping contributes to the photocatalytic activity over the entire absorbed wavelength range of <610 nm. Density functional theory calculations of electronic structures are performed to elucidate the possibility of bandgap narrowing upon nitrogen and carbon co‐doping on MMO structures.